Historical Explorations of Modern Epidemiology Patterns, Populations and Pathologies - Hakosalo, Heini; Parhi, Katariina; Sailo, Annukka (Medicine and Biomedical Sciences in Modern History, 2023)
XI, 270 p. 8 illus., 5 illus. in color.